GROSS LESIONS INDUCED BY NEMATODES OF BOTHROPS JARARACAAND BOTHROPS ALTERNATUS IN BRAZIL WITH TWO NEW RECORDS - Siqueira, Liege Renata (2009)
Results of fecal examinations have been compared with those obtained during necropsies of snakes infected with helminths. Stool samples from specimens of Bothrops jararaca and B. alternatus were investigated and three animals were positive for eggs during coprological screenings: one case representing authochtonous snake parasites, other related to species accidentally introduced together with naturally infected mice snakes fed on, and another with the association of both. Necropsies of those same specimens, showed the presence of the nematodes Ophidascaris travassosi Vaz, 1938, Kalicephalus costatus (Rudolphi, 1819), K. inermis Molin, 1861, Kalicephalus sp. and Acanthorhabdias acanthorhabdias Pereira, 1927. Bothrops jararaca is a new host record for O. travassosi and Bothrops alternatus for A. acanthorhabdias; the gross pathological lesions induced by the nematodes are reported.